Analisis Kinerja Lembaga Pendidikan Berdasarkan Metode Balance Scorecard (Studi Kasus Universitas Muhammadiyah Pontianak, Fakultas Ekonomi) - Santy Mayda Batubara (JURNAL MANAJEMEN MOTIVASI, 2015)
Performance measurement is used an institution or organization generally traditional, just measure the performance of the workers to produce something that was expected to achieve a goal. Workers are not required to innovate as a measure of performance is only intended to control the actions of any individual. The concept of the Balanced Scorecard (BSC), (financial perspective, customer perspective, internal business processes, and learning and growth perspective) is a method used by organizations that focus on strategies that fully understands the importance of embracing and uniting employees for an organization with. The advantages of this management system is able to show the outcome indicators and outputs, internal and external indicators, indicators of financial and non-financial, and indicators of cause and effect. Engineering analysis is univariate and bivariate analysis, using the secondary, using documentation and observation studies. The results of this study stated that the analysis of the performance with the use of the Balanced Scorecard method that has a significant value is the customer's perspective alone, the level of significance value of 0,004. Internal business processes, and learning and growth perspective is not able to be applied in this study, but is expected to be applied to subsequent research in order to create a better performance with the use of the Balanced Scorecard method.